Young people describe their prediagnosis cancer experience. Issue 11 (20th June 2013) - Gibson, Faith; Pearce, Susie; Eden, Tim; Glaser, Adam; Hooker, Louise; Whelan, Jeremy; Kelly, Daniel
Abstract: Objective: Young people often report a protracted journey to diagnosis and frequently report perceived delays. This study was undertaken to increase understanding of the self‐reported prediagnosis experiences in young people with a non‐haematological cancer, as close as possible to the time of diagnosis. Methods: Narrative interviews were conducted with 24 young people aged 16–24, 2–4 months from the diagnosis of a solid tumour. Data were analysed to identify whether prediagnosis narratives could be classified according to shared characteristics (typologies) to identify broader contextual issues concerning cancer, and cancer risk perceptions, in this age group. Case notes were also accessed to contextualize and confirm accounts. Results: The main themes, which included a group narrative concerning perspectives of delay, included the impact on an individual's everyday life by symptoms; the role that significant others in young peoples' lives played in the interpretation of symptom significance; the negotiation of entry into, and experiences of, generalist health care; entry into specialist care; and the threshold points that exemplified when events shifted and a diagnosis was eventually obtained. Conclusions: The narratives reveal complex, and multidimensional explanations for delay with individual and contextual factors contributing. Insights were gained into preventable diagnostic delay; including investigations having been instigated, but not followed up. Each narrative also offered significant insights into how cancer symptoms should be considered within the context of young peoples' lives. This would help prevent signs and symptoms in this age group failing to trigger suspicion and not being treated seriously. Copyright © 2013 John Wiley & Sons, Ltd.